Implementation of a LiFePO4 battery charger for cell balancing application - Amin Amin; Kristian Ismail; Abdul Hapid (National Research and Innovation Agency, 2018)
Cell imbalance has always happened in the series-connected battery. Series-connected battery needs to be balanced to maintain capacity and maximize the batteries lifespan. Cell balancing helps to dispart energy equally among battery cells. For active cell balancing, the use of a DC-DC converter module for cell balancing is quite common to achieve high efficiency, reliability, and high power density converter. This paper describes the implementation of a LiFePO4 battery charger based on the DC-DC converter module used for cell balancing application. A constant current-constant voltage (CC-CV) controller for the charger, which is a general charging method applied to the LiFePO4 battery, is presented for preventing overcharging when considering the nonlinear property of a LiFePO4 battery. The prototype is made up with an input voltage of 43V to 110V and the maximum output voltage of 3.75V, allowing to charge a LiFePO4 cell battery and balancing the battery pack with many cells from 15 to 30 cells. The goal is to have a LiFePO4 battery charger with an approximate power of 40W and the maximum output current of 10A. Experimental results on a 160AH LiFePO4 battery for some state of charge (SoC) shows that the maximum battery voltage has been limited at 3.77 volt and maximum charging current could reach up to 10.64 A. The results show that the charger can maintain battery voltage at the maximum reference voltage and avoid the LiFePO4 battery from overcharging.